MULTIMEDIA INTERAKTIF “KOPAJA” PENINGKATAN HASIL BELAJAR PESERTA DIDIK MATA PELAJARAN TATA BUSANA PROGRAM PAKET C - Suwarnoto - Suwarnoto (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2022)
The author developed a concept of learning interactive multimedia fashion by utilizing Information Technology (IT). The learning process by utilizing technology will make learning methods more passionate for students, so that students continue to be motivated to learn the subject of Dress Design. All learning components by the author are then arranged in a framework of Interactive Multimedia learning strategies "KOPAJA" (Communication, Participation, Network). This problem-solving strategy framework is translated into a real work paper and compiled as one of the written actions that can be useful as a breakthrough in addressing the problems above.